PRACTICE TEACHING PROBLEMS AND THEIR SOURCES: REFLECTION OF YEMENI EFL STUDENT TEACHERS - Hassan Saeed Ba-Udhan (State Islamic University of North Sumatra Indonesia, 2019)
The aim of this study is to investigate the major sources of EFL student teacher’s (STs’) problems of teaching practice (PT) and the main problems associated to the major sources. The target group consists of 50 STs majoring in English from the College of Education of Seiyun University, Yemen. The data of the study is collected using writing journals, questionnaire, and semi-structured interview. The problems included in the questionnaire are extracted from the entries of the writing journals and then classified into seven sources: 1) Student teachers, 2) pupils, 3) textbook, 4) school principal, 5) cooperating teacher, 6) school environment, and 7) gap between theory and practice. Results reveal that the first major source of the STs’ problems is the school environment, followed by gap between theory and practice. The third source of the problems is the pupils. The school environment, as revealed by the study, causes problems such as lack of teaching aids, large number of students, frequent cutoffs of electricity supply, and difficulty of arranging various activities in the classroom. On the other hand, the main problems related to the source of gap between theory and practice include difficulty of applying theories taught at the college, uselessness of literature courses taught at the college and feeling shock about the reality of teaching. Under the third source which is the pupils, the study asserts several main problems such as pupils’ heavy dependence on their teacher, their negative attitudes towards learning English, their weakness in English, and their habit of coming to the class unprepared.